Students' errors in solving HOTS mathematics problems based on newman's theory in view of learning independence - Setianingkrum, Reni; Utami, Nida Sri; Faiziyah, Nuqthy (Universitas Islam Negeri Raden Intan Lampung, 2025)
Mathematics plays a crucial role in developing students' cognitive skills, particularly at the junior high school level. One type of question commonly used in assessments is the Higher Order Thinking Skills (HOTS) question, which requires students to think critically, creatively, and analytically. However, many students still struggle with solving HOTS questions, often due to insufficient understanding of basic concepts, difficulties in applying those concepts, and low levels of self-directed learning. This study aims to provide an overview of student errors in solving HOTS problems based on Newman Theory in terms of learning independence. The method used in this research is a descriptive qualitative approach that worked on HOTS questions. Data were collected through tests, interviews, and self-directed learning questionnaires. The findings indicate that students' errors are largely related to challenges in concept mastery (K1), problem-solving strategies (K2), and a lack of independence in learning. Moreover, students with higher levels of self-directed learning performed better in solving HOTS questions. Based on these findings, it is recommended that educators implement teaching strategies that enhance students' self-directed learning, such as problem-solving activities and regular HOTS practice, to reduce errors in solving questions that require higher-level cognitive skills.